THE ANALYSIS OF THE RANGE OF ANTI-DECUBITUS PRODUCTS - D. T. Tanduyeva; E. O. Pagiyeva (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
The article presents the analysis of the range of anti-decubitus matrasses and pillows on the Russian market.